Pengenalan Aplikasi Elkopra Sebagai Perangkat Sistem Informasi Manajemen Keuangan Dalam Upaya Transformasi Digitalisasi Koperasi - Nugraha, Agus (LPPM Universitas Koperasi Indonesia, 2024)
Digitization of cooperatives is expected to be a strategic step to achieve efficiency and effectiveness of cooperative services without having to change the basic values ​​of the cooperative itself. This digitalization can be implemented in all aspects of cooperatives, namely: Governance, Marketing, Finance, Human Resources and Cooperative Operations. The existence of financial applications is very important to support the efficiency and effectiveness of cooperative financial management as well as a medium for improving the quality of information services to its members, one of which is the Elkopra Application. Through this cooperative digitalization transformation training, new insights have been opened for cooperative administrators in the digital era. Cooperatives must be adaptive to technological developments and the increasingly diverse needs of their members, even if this is done in stages